Trace metal contamination in Antarctic atmospheric deposition: insights from elemental and isotopic analysis of a snow pit at McCarthy Ridge, Victoria Land - Francisco Ardini; Alessia Chiaro; Matilde Mataloni; Elisa Cerri; Marco Vecchiato; Marco Grotti (Environmental Pollution, 2026)

Emerging contaminants during arctic rain-on-snow events: A case study from the 2023-24 Ny-Ålesund campaign - Azzurra Spagnesi; Stefania Gilardoni; Roberto Salzano; Matteo Feltracco; Beatrice Ulgelmo; Riccardo Maetzke; Francisco Ardini; Marco Grotti; Veronica L.M. Coppolaro; Tessa Viglezio; Simonetta Montaguti; Federico Scoto; et al. (Environmental Pollution, 2026)

Improving detection and figures of merit in single-particle inductively coupled plasma-mass spectrometry via transient event heights - Antonio Bazo; Lorién López-Villellas; Matilde Mataloni; Eduardo Bolea-Fernandez; Ana Rua-Ibarz; Marco Grotti; Maite Aramendía; Martín Resano (Analytica Chimica Acta, 2025)

Enhanced insight into the biogeochemical cycle of Hg in the Antarctic marine environment of Terra Nova Bay via isotopic analysis - Maria Alessia Vecchio; Lana Abou-Zeid; Laura Suàrez-Criado; Mathias Vandermeiren; Marco Grotti; Frank Vanhaecke (Chemosphere, 2025)

Elemental Distribution in Tissues of Shorthorn Sculpins (Myoxocephalus scorpius) from Kongsfjorden in Svalbard - Francisco Ardini; Federico Moggia; Davide Di Blasi; Paola Rivaro; Marco Grotti; Laura Ghigliotti (Journal of Marine Science and Engineering, 2024)
The shorthorn sculpin (Myoxocephalus scorpius) is considered a suitable sentinel species for marine pollution in the Arctic due to its ecology and stationary habits. To evaluate its role as a bioindicator for potential natural and anthropic impacts on the marine ecosystem of the Kongsfjorden (Svalbard, Norwegian Arctic), 33 female and male specimens of shorthorn sculpins were collected in July 2018 in proximity of the Ny-Ålesund international research facility and analyzed for the content of 25 major and trace elements and methylmercury (MeHg) in the muscle, liver, gonads, and gills by using spectroscopic techniques. Most elements had their maximum average concentrations in the gills (Al, Cr, Fe, Mn, Na, Ni, Pb, Se, Si, Sr, and V), while the livers featured higher contents of some toxic and heavy metals (As, Cd, Cu, Mo, and Zn). The muscle was characterized by high contents of Ca, K, and Mg, while Ba, Co, and P were mostly concentrated in the gonads. The gonads presented higher concentrations of Cr, K, Mg, Ni, P, and V for the males and Co, Cu, Fe, Mn, and Se for the females. Both the total Hg and MeHg concentrations in the muscle correlated with the fish size, indicating bioaccumulation, although high Se/Hg molar ratios (11.0 ± 2.2) suggested a low toxic potential of mercury.

Provenance of mineral dust deposited on Antarctica over the last sixty years by strontium isotopic analysis of snow from Dome C - Maria Alessia Vecchio; Marta Costas-Rodríguez; Laura Caiazzo; Federica Bruschi; Kasper Hobin; Frank Vanhaecke; Marco Grotti (Atmospheric Environment, 2024)

New insights into the sources of atmospheric lead reaching the Arctic by isotopic analysis of PM10 atmospheric particles and resuspended soils - Marco Grotti; Francisco Ardini; Maria Alessia Vecchio; Matilde Mataloni; Stefano Bertinetti; Federica Bruschi; Beatrice Moroni; David Cappelletti; Kasper Hobin; Frank Vanhaecke (Atmospheric Environment, 2024)

Elucidation of arsenic detoxification mechanism in Marchantia polymorpha: The role of ACR3 - Mingai Li; Aurélien Boisson-Dernier; Daniela Bertoldi; Francisco Ardini; Roberto Larcher; Marco Grotti; Claudio Varotto (Journal of Hazardous Materials, 2024)

Arsenic movement and fractionation in agricultural soils which received wastewater from an adjacent industrial site for 50 years - Cristiana Morosini; Elisa Terzaghi; Giuseppe Raspa; Marco Grotti; Stefano Armiraglio; Simone Anelli; Antonio Di Guardo (Science of The Total Environment, 2023)

Berlin statement on legacy and emerging contaminants in polar regions - Ralf Ebinghaus; Elena Barbaro; Susan Bengtson Nash; Cristina de Avila; Cynthia A. de Wit; Valeria Dulio; Janine Felden; Antonio Franco; Juergen Gandrass; Marco Grotti; Heike Herata; Kevin A. Hughes; et al. (Chemosphere, 2023)

Correction to: Progress on bringing together raptor collections in Europe for contaminant research and monitoring in relation to chemicals regulation - Paola Movalli; Guy Duke; Gloria Ramello; René Dekker; Al Vrezec; Richard F. Shore; Antonio García-Fernández; Chris Wernham; Oliver Krone; Nikiforos Alygizakis; Alexander Badry; Fausto Barbagli; et al. (Environmental Science and Pollution Research, 2019)

Progress on bringing together raptor collections in Europe for contaminant research and monitoring in relation to chemicals regulation - Paola Movalli; Guy Duke; Gloria Ramello; René Dekker; Al Vrezec; Richard F. Shore; Antonio García-Fernández; Chris Wernham; Oliver Krone; Nikiforos Alygizakis; Alexander Badry; Fausto Barbagli; et al. (Environmental Science and Pollution Research, 2019)

Trace elements in marine particulate and surface sediments of Kongsfjorden, Svalbard Islands - Francisco Ardini; Andrea Bazzano; Paola Rivaro; Francesco Soggia; Amanda Terol; Marco Grotti (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Sulfate source apportionment in the Ny-Ålesund (Svalbard Islands) Arctic aerosol - Roberto Udisti; Andrea Bazzano; Silvia Becagli; Ezio Bolzacchini; Laura Caiazzo; David Cappelletti; Luca Ferrero; Daniele Frosini; Fabio Giardi; Marco Grotti; Angelo Lupi; Mery Malandrino; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Elemental and lead isotopic composition of atmospheric particulate measured in the Arctic region (Ny-Ålesund, Svalbard Islands) - Andrea Bazzano; Francisco Ardini; Marco Grotti; Mery Malandrino; Agnese Giacomino; Ornella Abollino; David Cappelletti; Silvia Becagli; Rita Traversi; Roberto Udisti (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)